Examining the contribution of factors affecting the electrical behavior of poly(methyl methacrylate)/graphene nanoplatelets composites - Luo, Xiaoling; Schubert, Dirk W. (Journal of Applied Polymer Science, 2021)
In this study, poly(methyl methacrylate) (PMMA)/graphene nanoplatelets (GNPs) conductive composite films with different morphologies were fabricated from the same constituent materials using four fabrication techniques, solution casting (SC), SC followed by hot pressing (SCP), melt mixing followed by SC (MSC), and melt mixing followed by hot pressing (MP). Morphologies of dispersed GNPs and electrical properties in both in‐plane and perpendicular direction were investigated and compared systematically. The corresponding percolation thresholds (Φc) of the composites varied from 0.42 ± 0.13 vol% to 3.26 ± 0.48 vol%. The conductivities varied up to two orders of magnitude and decreased in the sequence of SC > MSC > SCP > MP. These variations were explained in terms of GNPs size, GNPs orientation, distribution and dispersion state of fillers. The contribution of the above factors in each procedure were discerned individually, the results were discussed and compared with other experimental studies and simulations as well.<br
Keywords: films; morphology; nanostructured polymers; nanotubes; graphene and fullerenes; theory and modeling